The relationship between the quality of hospital care and COVID-19 inpatients’ satisfaction in medical centers in Ilam, Iran - Majideh Heravi-Karimooi; Somaye Javanmardnejad; Nahid Rejeh (Payesh, 2023)
Objective(s): This study was conducted to determine the satisfaction of patients admitted to medical centers in Ilam in 2020-2021. Methods: This was a cross-sectional study of 200 patients who admitted with Covid-19 in medical centers of Ilam, Iran, from December 21, 2020 to March 21, 2021. Data collected using a questionnaire on demographic information and symptoms, a short form Quality from the Patient's Perspective (QPP-12) and Patient Satisfaction Index (PSI). The data was analyzed using SPSS version 22. Results: The mean age of patients was 49.62±15.05. The mean quality score of hospital care from the patients' point of view was 46.99±5.83, and in 83% of cases, the quality of care was optimal. Also, the mean satisfaction score of the patients was 3.47±0.34 and 87% of the patients expressed moderate satisfaction. Patient satisfaction and quality of care showed a positive and significant relationship P<0.001). Conclusion: The quality of care can play an important role in improved patients’ satisfaction.